Lagoas marginais do alto-médio curso do rio São Francisco: dinâmica hidrogeomorfológica, geocronologia e impactos ambientais - Wallace Magalhaes Trindade (2016)
Marginal lagoons are river systems features generated in flood-plains water courses and tend to accumulate sediments, nutrients and contaminants. Sediments deposited in these lagoons serve as records of current and past environmental conditions. In São Francisco River Valley, marginal lagoons are characteristic features with great ecological importance. However geochemical and geomorphological aspects of these environments are poorly studied. The main objective of this study was to analyze the role of marginal lagoons as hydro-geomorphologic evidence of fluvial dynamics and environmental impacts of anthropogenic pressures in the upper-middle São Francisco River, in order to establish correlations between the concentrations of heavy metals and the intensification of uses and occupation of the land in the last 100 years. Six marginal lagoons were selected where sediment cores were sampled with the aid of a sampler developed in this research. The techniques and procedures adopted involved the analysis of the mineralogical phases by X-Rays Diffraction, determination of chemical composition by X-Rays Fluorescence, particle size analysis by laser diffraction and the pipette method, in addition to determining the organic matter content, dating of sediments by 210Pb method and quantification of extractable heavy metals (Ni, Cu, Pb and Zn) by Optical Emission Spectrometry (ICP-OES).The mineralogical composition of sediments marked by quartz, feldspar and mica reflects the strong influence of regional geological framework where arkoses sandstones of the Três Marias Formation (Bambuí Group), are the main source of sediment. Major elements found in X-Ray fluorescence are consistent with the mineral phases, indicating the predominance of Si, Al, Fe, K and Ti. On the other side the trace elements showed a behavior and concentrations highly variable with tendencies of enrichment in surface layers, indicating anthropogenic contributions. The results of particle size laser analysis indicate a stratigraphy dominated by fine sediments at the top of the cores. However, the occurrence of sandy layers interleaved with fine sediments forming abrupt layers at depths greater than 180 cm are an indication of a hydrodynamic marked by pulses of past floods that promoted breaches of the levees. The results of 210Pb indicated a sedimentation rate of 0.2 cm.year-1, where it is possible to evaluate the effect of human activities over the past 100 years. The history of metal contamination in the study area covered a period of 50 years between 1965 and 2015. During this period, it was observed that anthropogenic activities, mainly agricultural practices, are contributing to the suppression of native vegetation and the input of organic matter, as well as increasing the concentrations of heavy metals in the sediments of the marginal lagoons. The geochronological data and the concentrations of heavy metals indicated that the last 50 years, as the savannah was replaced by monocultures of eucalyptus, Pinus, soy, coffee and other crops, an amount of 76.60 tons of Cu, 227 97 of Pb and 474.14 of Zn were incorporated into the sediments.